2020
DOI: 10.4491/eer.2020.027
|View full text |Cite
|
Sign up to set email alerts
|

Toward greener membranes with 3D printing technology

Abstract: 3D printing has recently influenced membrane science. As a green alternative to current membrane fabrication methods, 3D printing prevents the mixing of highly toxic chemicals into water through its sustainable production. Furthermore, the risk of exposure to these toxic materials and of mechanical accidents during the fabrication is also attenuated. This type of in-situ fabrication eliminates logistic-based problems caused by transportation and packaging. Eliminating packaging and reducing transportation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…[86] The high price of the existing 3D printers, particularly highresolution ones, like poly-jet type printers, is another drawback of current technology. [34] One issue that serves as a limitation to the adoption of 3D printers at industrial scale is the lack of broad assessments to explain its economic feasibility in terms of the total production cost for water and wastewater treatment applications. For instance, Thomas et al [15] concluded that the commercial-scale application in membrane distillation is limited by the cost of fabricating 3D-printed components.…”
Section: Commercialization Of 3d-printed Membranes and Its Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…[86] The high price of the existing 3D printers, particularly highresolution ones, like poly-jet type printers, is another drawback of current technology. [34] One issue that serves as a limitation to the adoption of 3D printers at industrial scale is the lack of broad assessments to explain its economic feasibility in terms of the total production cost for water and wastewater treatment applications. For instance, Thomas et al [15] concluded that the commercial-scale application in membrane distillation is limited by the cost of fabricating 3D-printed components.…”
Section: Commercialization Of 3d-printed Membranes and Its Challengesmentioning
confidence: 99%
“…[9,33] The environmental friendliness of 3D printing as an alternative method to current membrane fabrication techniques was studied as well. [34] In this review paper, we emphasize the recent progress of 3D printing technology for membrane separation, focusing on water and wastewater decentralized systems.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the thermal performance of BNNTs can be further benefited by employing thermal membrane systems such as for membrane distillation and pervaporation. By also considering the advantages and the recent boost in 3D printed membranes [ 113 , 114 , 115 , 116 ], BNNTs should also be considered for that field.…”
Section: Perspectives On Key Membrane Studiesmentioning
confidence: 99%
“…Previous studies employed computational fluid dynamics (CFD) to investigate the effect of spacer shapes, including nonwoven, woven, middle layer, and fully woven spacers [ 21 ]; 30°, 45°, 62°, and 90° spacer filaments [ 22 ]; hairy spacers [ 23 ]; saw-tooth spacers [ 24 ]; zigzag spacers [ 25 ]; multi-layer spacers [ 26 ]; and sinusoidal spacers [ 27 ], on the membrane performance. In addition, with the boost of 3D printing, the design of spacers was affected [ 28 , 29 ], i.e., column-type spacers [ 30 ], triply periodic minimal surfaces (TPMS) spacers [ 31 ], symmetric perforated spacers (1-Hole, 2-Hole, and 3-Hole) [ 32 ], and honeycomb spacers [ 33 ], were fabricated by 3D printing. In addition, 3D printing provides material selection for spacer fabrication.…”
Section: Introductionmentioning
confidence: 99%